CACTO DEVELOPMENT: CARE PROGRAM FOR MOTHERS OF CHILDREN WITH CONGENITAL ZIKA SYNDROME. - Lima Falcão do Vale, Paulo Roberto; Passos Costa, Jessica Santos; Freitas, Katia Santana; Lacerda, Maria Ribeiro; de Carvalho, Rosely Cabral; de Santana Carvalho, Evanilda Souza (Texto & Contexto Enfermagem, 2023)
Objective: to develop a unitary caring program for mothers of children with Congenital Zika Syndrome. Method: this is a methodological study, based on Unitary Caring Science, developed in two phases: creation, consisting of six moments, and content validity, through the participation of 36 experts on the subject, professional caregivers and mothers. The Content Validity Index and the Content Validity Ratio were used for data analysis. Results: the program was named CACTO, composed of seven care modalities: Taking care of my mind; Upright and correct position; Taking care of my sleep; Family that is together; Mirror mirror on the wall; Mother who takes care of mother; Facing prejudices. CACTO was validated with a Content Validity Index ≥0.88 and critical Content Validity Ratio values greater than or equal to the cutoff point defined for each group of experts. Conclusion: the translation of Unitary Caring Science into a care program encourages professionals to promote innovative care, valuing acceptance, autonomy, citizenship and critical awareness, advocating in favor of emancipatory interactional care. CACTO is a technological innovation that can transform professional care, promote the resolution of mothers' health needs and enhance the quality of life of children with Congenital Zika Syndrome, family and caregivers themselves.